Karakterisasi Sifat Kimia Crackers Ikan Tongkol Dengan Variasi Penambahan Tepung Ikan Tongkol (Euthynnus Affinis) - Ara Nugrahayu Nalawati; Danu Indra Wardhana; Asih Imer Rita; Isya Lestari Triyudhani (Journal of Food Industrial Technology, 2024)
In general, crackers have a very high flour content and low protein content because they do not require too much dough expansion. The protein content of crackers sold commercially is only sufficient for around 5-8% of daily protein requirements. So it is necessary to substitute the basic ingredients for wheat flour with other flour ingredients that have a high protein content, one of which is tuna fish flour. This research aims to determine the best ratio and length of drying time for the chemical characteristics, color, aroma, taste and preferences of the crackers that the panelists like, as well as the shelf life of the tuna crackers. The parameters and tests used in this research include: water content, ash content, fat content, protein content, swelling power, and organoleptic tests (taste, color, aroma, preference). The research results showed that crackers with the addition of tuna fish flour met the quality requirements of SNI 01-2973-1992. The tuna fish flour cracker formulation has a water content of 0.4%, ash content of 0.2%, protein content of 7.11%, fat content of 16%, and swelling power of 0.6%.